A Review of Developmental and Reproductive Toxicity of CS2 and H2S Generated by the Pesticide Sodium Tetrathiocarbonate. (15th March 2013) - Silva, Marilyn
<x xml:space="preserve">Abstract</x> BACKGROUND Sodium tetrathiocarbonate (STTC) is an example of a pesticide that when prepared for use in aqueous solution releases two toxic products carbon disulfide (CS2) (active ingredient) and hydrogen sulfide (H2S) in ambient air in equimolar concentrations resulting in potential exposure to workers and bystanders. CS2 and H2S are pollutants that are generated from several pesticides as well as in industrial settings. METHODS Registrant submitted reports and open literature studies for STTC, CS2 and H2S were reviewed. Previous reports suggest that CS2 was a concern as a developmental and reproductive toxicant. H2S was also examined since it is a neurotoxicant and potentially harmful to developing fetuses. RESULTS STTC did not induce developmental or reproductive effects in animal studies. CS2 was a developmental neurobehavioral toxin in rat pups (inhalation no observed effect level [NOEL] = 0.01ppm). Reproductive effects occurred in male and female factory workers after CS2 exposure (NOEL = 1ppm). H2S had developmental effects in rats at doses at or above those observed for nasal pathology (NOEL = 10ppm) but was not a reproductive or developmental toxin in humans. CONCLUSIONS The database for CS2 indicates a strong potential for developmental neurotoxicity in animals at low doses but it is lacking in acceptable, well‐performed studies. There is also a lack of studies performed with CS2 and H2S as a mixture.